2009
DOI: 10.2337/dc09-0197
|View full text |Cite
|
Sign up to set email alerts
|

Use of Multiple Metabolic and Genetic Markers to Improve the Prediction of Type 2 Diabetes: the EPIC-Potsdam Study

Abstract: OBJECTIVEWe investigated whether metabolic biomarkers and single nucleotide polymorphisms (SNPs) improve diabetes prediction beyond age, anthropometry, and lifestyle risk factors.RESEARCH DESIGN AND METHODSA case-cohort study within a prospective study was designed. We randomly selected a subcohort (n = 2,500) from 26,444 participants, of whom 1,962 were diabetes free at baseline. Of the 801 incident type 2 diabetes cases identified in the cohort during 7 years of follow-up, 579 remained for analyses after exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
145
1
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(165 citation statements)
references
References 16 publications
15
145
1
4
Order By: Relevance
“…Combining information on FPG or impaired fasting glucose with a simple diabetes risk score has been reported to increase predictive ability [7,8,[12][13][14][15][16][17]. A study reported that screening models using the combination of HbA 1c , BMI and FPG accurately identified individuals at risk of future clinically diagnosed diabetes [22], although the factors that remained significant were different from those found in the present study.…”
Section: Discussioncontrasting
confidence: 51%
See 3 more Smart Citations
“…Combining information on FPG or impaired fasting glucose with a simple diabetes risk score has been reported to increase predictive ability [7,8,[12][13][14][15][16][17]. A study reported that screening models using the combination of HbA 1c , BMI and FPG accurately identified individuals at risk of future clinically diagnosed diabetes [22], although the factors that remained significant were different from those found in the present study.…”
Section: Discussioncontrasting
confidence: 51%
“…On the other hand, adding complex data such as the results of oral glucose tolerance tests and measurements of insulin levels and inflammatory markers into a simple clinical model only minimally improves risk prediction while increasing cost and inconvenience [10,19]. Similarly, adding genetic information to conventional risk factors does not appear to greatly refine the prediction of diabetes risk [14,20,21].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A substantial increment of c statistics is possible if these prediction models do not contain a measure of glycaemia [75]. However, protein-based biomarkers that not only lead to statistically significant, but also to clinically relevant improvements of model accuracy remain to be identified for models that already consider glucose or HbA 1c [18,35,[76][77][78][79][80], as summarised in a recent review [39].…”
Section: Peptides and Proteinsmentioning
confidence: 99%